Factores asociados a los intentos de suicidio en pacientes atendidos en el Centro de Salud Catacocha, Tipo B - Bustos Salcedo, Estefany Daniela (2022)
The suicide attempt is a behavior by which the subject seeks to harm himself with the aim of achieving his death, but his actions do not end in the expected result. This research had as main objective to identify the factors and main motivations associated with suicide attempts in patients treated at the Catacocha Health Center. A methodology with a quantitative, descriptive, exploratory, approach was proposed by reviewing the care matrix and applying a semi-structured survey, the Suicidal Ideation Scale, the family Apgar and the Beck Depression Inventory to its subsequent univariate descriptive analysis, establishing the frequency of each variable. The analysis of the results indicates that the behavior was more frequent in males, between the ages of 11 and 20, with single marital status and incomplete secondary schooling. In addition, medium suicidal ideation, low family satisfaction, and severe depression were determined and finally the main motivations for making a suicide attempt on his life were the economic situation, family problems and sexual abuse or harassment.